Steam gasification of lignite and biomass with integrated syngas cleaning for decentralized SNG production - Treiber, Peter (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
The production of substitute natural gas from solid feedstocks involves thermochemical gasifica-tion, syngas cleaning, and catalytic methanation as key processes. Feedstocks as lignite or biomass are gasified with steam at temperatures above 800 °C and at a pressure of 5 bara or above. In contrast to other dual fluidized bed gasifiers, the Heatpipe Reformer technology can produce syngas at the ideal conditions for subsequent methanation. The pressurized synthesis gas is rich in hydrogen and essentially contains no nitrogen. However, the raw syngas has to undergo different cleaning steps before it can be fed to the methanation reactor to avoid catalyst poisoning. Aiming at decentralized small- to mid-scale plants, the applied gas cleaning technology has to be very effective while requiring as little investment costs as possible. Compared to large-scale cold methanol scrubbing, hot potassium carbonate scrubbing offers the required features as a suitable gas cleaning process. At last, optimization of the process combination can lead to an optimum operating point where high capital costs can be traded for minor catalyst consumption due to the bulk syngas cleaning capacity of the carbonate scrubbing process. Within the European research project CO2freeSNG2.0, this process chain is investigated in detail for the production of substitute natural gas from lignite. Considering the available literature, the Heatpipe Reformer is chosen as gasifying technology to be coupled with the Benfield process for syngas cleaning while methanation is performed with commercial nickel catalysts. Besides the pressurized steam gasification, the hot potassium car-bonate scrubbing is the key subject of this thesis. To evaluate the hot potassium carbonate scrubbing in a commercial size environment, a 50 MW lignite-to-SNG process chain is simulated under equilibrium conditions. Based on this simulation, the necessary mass and energy flows and the required removal efficiency for CO2 are defined. Also, a 100 kW rate-based simulation is set up for the dimensioning of the pre-pilot-scale syngas scrubbing unit at the Chair of Energy Process Engineering, Friedrich-Alexander-University Erlangen-Nürnberg. The experimental part of this thesis is performed at the bench scale and is based on syngas generation by a 5 kW pressurized fluidized bed steam gasifier. To be able to determine the influence of the syngas scrubbing, the gasification process is investigated with a focus on syngas quality and contaminants such as tars and sulfur components. Downstream the gasifier, a bench-scale syngas scrubber operating on a solution of 30 wt.-% potassium carbonate in water is added to the process line. The cleaned syngas is tested for gas composition and the scrubbing process is rated based on the removal efficiency of sour gases and the influence of the scrubbing process on other contaminants in the syngas. At last, the complete process chain is demonstrated on a 100 kW Heatpipe Reformer, a pre-pilot-scale Benfield scrubber, and a slipstream methanation reactor. The influence of wall and scale effects can, therefore, be minimized while the general results from the bench-scale tests are validated. The results prove the general capability of the hot carbonate scrubber as bulk sour gas removal and demonstrate the influence of process parameters in gasification and gas cleaning on the syngas quality.<br
Keywords: Vergasung; Biomasse; Braunkohle; Synthesegas; Benfield process; Carbonate scrubbing; Gasification; Syngas Cleaning